Here's the question you clicked on:

55 members online
  • 0 replying
  • 0 viewing

Fox375

  • 3 years ago

If you were to use the elimination method to solve the following system, choose the new system of equations that would result after the variable z is eliminated in the first and second equations, then the second and third equations. 3x – 7y – z = –14 3x + 3y + 2z = 1 2x + 5y – 2z = –16 3x – 7y = –14 2x + 5y = –16 9x – 11y = –27 5x + 8y = –15 9x – 11y = –27 3x – 7y = –14 2x + 5y = –16 5x + 8y = –15

  • This Question is Closed

    Not the answer you are looking for?
    Search for more explanations.

    • Attachments:

Ask your own question

Sign Up
Find more explanations on OpenStudy
Privacy Policy